Fantasies of Nina Simone - Stein, Jordan Alexander (Duke University Press, 2024)
"Fantasies of Nina Simone mines the tension between our collective and individual fantasies of Nina Simone (1933-2003) the performer, Civil Rights activist, and icon, and Nina Simone's desires for herself as an ordinary person. Simone has long embodied the contradictions that Black womanhood has been made to bear in our culture: beauty and dignity, abjection and power, expansive personal talent limited by narrow opportunities for advancement, while also being tasked with resolving these contradictions. Working through Simone's biography and her scattered public archive, Jordan Alexander Stein maps two major movements in her work: her early covers of white male pop song writers and her later move to exploring Caribbean and Afro-diasporic sound, analyzing these shifts as Simone's movement towards her desires, first for authority and authorship and second for her own becoming. Looking at examples from across Simone's genre-bending, four-decade career and at her work's many uptakes and afterlives, Fantasies of Nina Simone mobilizes the psychoanalytic concept of fantasy to build a Black feminist history with and for this multi-faceted performing artist"--
Keywords: Simone, Nina -- 1933-2003; Simone, Nina / 1933-2003; African American women singers / Biography; Women singers / United States / Biography; Singers / United States / Biography; Feminism and music / United States / History / 20th century; Womanism / United States; Chanteuses noires américaines / Biographies; Chanteuses / États-Unis / Biographies; Chanteurs / États-Unis / Biographies; Féminisme et musique / États-Unis / Histoire / 20e siècle; Womanisme / États-Unis; SOCIAL SCIENCE / Ethnic Studies / American / African American & Black Studies; Electronic books; Biografie